2018
DOI: 10.1101/435941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of enteroaggregativeEscherichia coliwithin the ST131 lineage as a cause of extraintestinal infections

Abstract: 26Escherichia coli sequence type 131 (ST131) is a major cause of urinary and bloodstream infections 27 and its association with extended-spectrum β-lactamases (ESBL) significantly complicates treatment. 28 Most notorious is its rapidly expanding H30-Rx clade (named for containing allele 30 of the type-1 29 fimbrial adhesin gene fimH and extensive antimicrobial resistance), which appears to have emerged 30 55 Escherichia coli sequence type 131 (ST131) is the dominant multidrug-resistant (MDR) 56 extrai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…We believe that the presence of such melting pots is a phenomenon during pathogen evolution even more common than expected. Recent data from Boll et al (57) corroborate our hypothesis: they isolated ST131 E. coli, the most prevalent multidrug-resistant ExPEC lineage globally, from current community-acquired bacteremia and recurrent UTI cases in Denmark and found acquisition of the EAECdefining virulence plasmid pAA and of additional ExPEC genes, thereby enhancing the ability to successfully colonize and subsequently infect humans (57). We speculate that in-depth analysis of all available ST131 E. coli strains could reveal the existence of other hybrids within ST131 E. coli and further affirm our hypothesis that heteropathogenicity is a common phenomenon of pathogenic E. coli strains.…”
Section: Discussionsupporting
confidence: 69%
“…We believe that the presence of such melting pots is a phenomenon during pathogen evolution even more common than expected. Recent data from Boll et al (57) corroborate our hypothesis: they isolated ST131 E. coli, the most prevalent multidrug-resistant ExPEC lineage globally, from current community-acquired bacteremia and recurrent UTI cases in Denmark and found acquisition of the EAECdefining virulence plasmid pAA and of additional ExPEC genes, thereby enhancing the ability to successfully colonize and subsequently infect humans (57). We speculate that in-depth analysis of all available ST131 E. coli strains could reveal the existence of other hybrids within ST131 E. coli and further affirm our hypothesis that heteropathogenicity is a common phenomenon of pathogenic E. coli strains.…”
Section: Discussionsupporting
confidence: 69%
“…Poultry intestinal carriage of extra-intestinal pathogenic E. coli (ExPEC) which causes extra-intestinal disease in humans may be of epidemiological relevance and concern as the STs found are similar to the most prevalent STs from this study [40][41][42][43]. E. coli has been identified in both eggs and poultry meat [28,31,44,45] which may serve as a vector for E. coli Moreover it is suggested that certain lineages within ST131 have acquired traits which may favor intestinal colonization despite being characterized as ExPEC [46].…”
Section: Discussionmentioning
confidence: 61%
“…These EAEC isolates were not previously described as hybrid strains and originated from cases of diarrhoeal disease in England [40]. However, hybrid EAEC/ExPEC strains are known to cause UTI outbreaks [119,120]. EAEC strains carry most of their virulence cargo on plasmids and are renowned for prolific biofilm formation [121].…”
Section: Class 1 and 2 Integronsmentioning
confidence: 99%